The Primordial Radionuclides Activity Concentrations and Associated Minerals in Rocks from Selected Quarries in Northern Uganda - Olanya, Amos; Denis Okello; Bosco Oruru; Akisophel Kisolo (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2022)
The primordial radionuclides (PR) activity concentrations and associated minerals in 20 rock samples from Gulu and Amuru district quarries were determined using Na (Tl) gamma ray spectrometer and Transmitted Light Microscope (TLM). These were carried out at Physics and Geology Departments of Makerere University, Kampala in Uganda. The PR activity concentrations, the gamma dose rates, and the radiological hazard indices were all determined to assess the radiological hazards and risks of the exposure on the quarry workers and on the inhabitants. The minerals were obtained to determine whether minerals containing PR were highly radioactive. The computed PR activity concentrations from the five quarries ranged from 4.1 ± 1.7 to 207.6 ± 6.5 for 238U, 7.0 ± 2.0 to 452.0 ± 2.3 for 232Th, and 8.6 ± 2.0 to 2055.4 ± 73.1 Bq kg-1 for 40K, respectively with averages of 57.1 ± 4.7, 122.3 ± 11.1, and 914.2 ± 30.3 Bq kg-1. These values were found to be above the world limit of 33.0, 45.0 and 420.0 Bq kg-1 by 1.7, 2.7, and 2.2 factors. The computed average values of absorbed gamma dose rates (D), annual effective dose equivalent outdoor (Eo), excess lifetime cancer risk (ELCR), radium equivalent activity (Raeq), external hazard index (Hex), internal hazard index (Hin) and gamma index (I) for the five quarries were 134.58 ± 10.13 nGy h-1, 0.34 ± 0.03 mSv yr-1, 1.07 ± 0.09 x 10-3, 294.08 ± 17.88 Bq kg-1, 0.80 ± 0.06, 0.93 ± 0.05 and 1.35 ± 0.09, respectively. The computed average values of D, Eo and ELCR for the five quarries were above the world limit by factors of 2.2, 4.9, and 3.7, respectively. Therefore, quarry workers and the inhabitants were exposed to PR hence significant health risks associated with induced cancer and gene mutation. However, average values of Raeq, Hex, and Hin were found to be below the world limit except for one of the quarry sites. Although the studied rocks could be used as building materials without causing external diseases and respiratory infections, the average value of, I, showed that studied rocks should be used in moderation to limit the radiological hazards except for Palukere rocks. Mineralogical analyses has also shown the presence of quartz, potassium feldspar, plagioclase, biotite, muscovite, and opaque minerals. Quartz was the major mineral while the rest were accessories. The results of this study could be used by different institutions such as Uganda Atomic Energy Council (AEC) that protects the environment from dangers resulting from ionizing radiation. This body could assist to advise quarry workers on good practices. The National Environmental Management Authority (NEMA) that controls environmental systems should ensure that Gulu and Amuru districts work in line with set principles on environment, and where necessary to enforce the quarry by-laws and ordinances. To urge the Directorate of Geological Survey and Mines (DGSM) to also conduct geological studies for valuable radioactive minerals in the study areas of Gulu and Amuru districts. The Uganda Ministry of Health (MoH) experts could also carry out additional studies to establish the correlation of cancer infections and quarry works. This would inform the government on corrective measures that protects the population of the region.